Association of perinatal risk factors with neurological outcome in neonates with hypoxic ischemic encephalopathy. (3rd April 2021) - Scheidegger, S.; Held, U.; Grass, B.; Latal, B.; Hagmann, C.; Brotschi, B.; ,
Abstract: Objective: Neonates exposed to perinatal insults typically present with hypoxic ischemic encephalopathy (HIE). The aim of our study was to analyze the association between known risk factors for HIE and the severity of encephalopathy after birth and neurological outcome in neonates during the first 4 d of life. Methods: Retrospective cohort study including 174 neonates registered between 2011 and 2013 in the National Asphyxia and Cooling Register of Switzerland. Results: None of the studied perinatal risk factors is associated with the severity of encephalopathy after birth. Fetal distress during labor (OR, 2.06; 95% CI, 1.02–4.25, p  = .049) and neonatal head circumference (HC) above 10th percentile (p10) at birth (OR, 1.33; 95% CI, 1.05–1.69, p  = .02) were associated with neurological benefit in the univariate analysis. Fetal distress on maternal admission for delivery was the only risk factor for neurological harm in the univariate (OR, 0.26; 95% CI, 0.12–0.57, p  < .01) and the multivariate analysis (OR, 0.15; 95% CI, 0.04–0.67, p  = .013). We identified two different patient scenarios: the probability for neurological benefit during the first 4 d of life was only 20% in neonates with the combination of all the following risk factors (gestational age >41 weeks, chorioamnionitis, fetal distress on maternal admission for delivery, fetal distress during labor, sentinel events during labor, HC below 10th percentile), whereas in the absence of these risk factors the probability for neurological benefit increased to 80%. Conclusions: We identified a constellation of risk factors that influence neurological outcome in neonates with HIE during the first 4 d of life. These findings may help clinicians to counsel parents during the early neonatal period. (ClinicalTrials.gov NCT02800018).